Water and sediment quality in the upper reaches of the Sampadi river - Then, Shirley (Universiti Malaysia Sarawak, UNIMAS, 2012)
This study was done to identify the water and sediment quality at the upper reaches of the Sampadi River where only few stations had been monitored before. There are oil palm plantations and mill, some residential areas and coal refinery situated at the upper reaches of this river. Sampling was done during low tide and high tide conditions. Total suspended solids (TSS) concentration was high during low tide which ranged from 39.93-56.07 mg/L. Nitrate and nitrite nitrogen also show higher concentrations during low tide. However, five-day biochemical oxygen demand (BOD5), total Kjeldahl nitrogen (TKN) and ammonia nitrogen concentration were found higher in high tide condition. BOD5 ranged from 2.81 to 5.02 mg/L during high tide while it ranged from 1.78 to 4.30 mg/L during low tide. TKN and ammonia nitrogen were found to be high in Station 2 and 3 during low and high tide, respectively. This is due to the nutrients input from the oil palm plantation at Chupin Besar River. However, based on the National Water Quality Standard of Malaysia, most of the water quality parameters in stations was categorised under Class I and II. Meanwhile, oil and grease is categorized in Class 3 and for nitrate nitrogen, nitrite nitrogen and phosphorus in water, they are categorized in Class 2 and Class E of the Malaysia Marine Water Quality Criteria and Standard. As for sediment quality in this river, it is influenced by the particle size distribution in the stations where finer particles like silt showed higher total organic carbon (TOC) percentage, heavy metals and nutrients concentrations. There are significant negative correlations between sand and TOC (r=-0.933); between sand and TKN (r=-0.689); and between sand and total phosphorus (r=-0.970).